Changes in insulin sensitivity and secretion after sleeve gastrectomy. Issue 3 (9th November 2015) - Casella, G; Soricelli, E; Castagneto-Gissey, L; Redler, A; Basso, N; Mingrone, G
Abstract: Background: Sleeve gastrectomy is indicated for the treatment of obesity and related co-morbidity including diabetes. The dynamic changes in insulin secretion and sensitivity after sleeve gastrectomy are unknown. Methods: Whole-body insulin sensitivity was measured by the euglycaemic hyperinsulinaemic clamp technique, and insulin secretion by C-peptide deconvolution after an oral glucose tolerance test (OGTT), before and 3, 6 and 12 months after sleeve gastrectomy in morbidly obese subjects. The time course of glucagon-like peptide (GLP) 1, as a marker of insulin secretion following OGTT, was also assessed. Results: Ten patients were included in the study. Median (range) baseline insulin sensitivity (M-value) increased from 84·0 (20·2–131·4) mmol per kg per min at baseline to 122·8 (99·0–179·3) mmol per kg per min at 12 months after surgery ( P = 0·015). Fasting insulin sensitivity, measured by homeostatic model assessment of insulin resistance, which represents a surrogate index of hepatic insulin resistance, decreased from 3·3 (1·9–5·5) to 0·7 (0·5–1·1) mg/dl·µunits/ml ( P < 0·001). Total insulin secretion, measured as incremental area under the curve (AUC), after OGTT decreased from 360·4 (347·9–548·0) to 190·1 (10·1–252·0) mmol/l·180 min at 12 months ( P = 0·011). The AUC for GLP-1 increased from 258·5 (97·5–552·6) to 5531·8 (4143·0–7540·9) pmol/l·180 min at 12 months after sleeve gastrectomy ( P < 0·001). In multiple regression analysis, 51 per cent of the M-value variability was explained by GLP-1 secretion. Conclusion: Sleeve gastrectomy improved insulin sensitivity and reduced insulin secretion within 6 months after surgery. Although there was a correlation between insulin sensitivity and bodyweight, the major driver of the improvement in insulin sensitivity was GLP-1 secretion. Abstract : Improves insulin sensitivity, reduces insulin secretion